Resistance to antibacterial drugs and bacteriophages of Klebsiella pneumoniae isolates isolated from children of different ages with intestinal infections - N. V. Gonchar; A. K. Kopersak; N. V. Skripchenko; A. S. Kvetnaya; A. M. Moskalyuk; K. D. Ermolenko; E. I. Ermolenko; S. G. Grigor'ev (Детские инфекции (Москва))
The aim is to study the antibiotic and phage resistance of K. pneumoniae strains isolated from children with acute intestinal infections. Materials and methods. 490 K. pneumoniae strains isolated by the bacteriological method from feces from patients with intestinal infections of various etiologies aged from 1 month to 18 years in the period 2019—2021 were studied. The diagnosis of intestinal infection caused by K. pneumoniae was established taking into account the detection of the pathogen at a concentration of at least 5 lg CFU/g (n = 283; 57.8%). Children with Klebsiella seeding, made up three age groups: from 1 to 12 months of life (n = 245; 50%); from 1 to 3 years (n = 131; 26.7%); from 3 to 18 years (n = 114; 23.3%). Results. A higher frequency of K. pneumoniae seeding in high concentrations from fecal samples of children with intestinal infections aged from 1 to 12 months was established (?2 = 14.24; p < 0.001). Analysis of the frequency of K. pneumoniae resistance to antimicrobials revealed its increase to ampicillin/sulbactam from 4.2 ± 1.6% to 9.7 ± 1.9% and to gentamicin from 3.0 ± 1.3% to 7.6 ± 1.7% (p < 0.05) with an increase in the concentration of the pathogen from 3—4 to 5—6 lg CFU/ml. In K. pneumoniae strains isolated in low concentrations, resistance to polyvalent anti-klebsiella bacteriophage was significantly higher than to monovalent bacteriophage. Conclusion. Children of the first year of life belong to the risk group for the development of klebsiella intestinal infection. An increase in the frequency of K. pneumoniae resistance to ampicillin/sulbactam and gentamicin correlates with an increase in the concentration of the pathogen in fecal samples.